2018
DOI: 10.1007/s00415-018-8827-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of on-going treatment with angiotensin-converting enzyme inhibitor or angiotensin receptor blocker on the outcome of patients treated with intravenous rt-PA for ischemic stroke

Abstract: In patients treated by intravenous thrombolytic therapy for ischemic stroke, on-going treatment with ACE-Is or ARBs does not influence on outcomes after adjustment on baseline characteristics and propensity scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous studies rarely considered ICH as a major outcome. Recently, Gilliot et al 23 found that on-going treatment with ACE inhibitor or ARBs did not influence hemorrhagic transformation occurrence in a cohort of patients solely treated with intravenous thrombolysis. Of note, in the BP TARGET trial, hemorrhagic transformations consisted of all ICH after EVT, given their deleterious impact on long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies rarely considered ICH as a major outcome. Recently, Gilliot et al 23 found that on-going treatment with ACE inhibitor or ARBs did not influence hemorrhagic transformation occurrence in a cohort of patients solely treated with intravenous thrombolysis. Of note, in the BP TARGET trial, hemorrhagic transformations consisted of all ICH after EVT, given their deleterious impact on long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these studies did not assess conventional end points in the acute phase (ie, ICH, National Institutes of Health Stroke Scale [NIHSS] score at 24 hours) and concerned heterogeneous AIS cohorts, with different stroke causes (small vessel disease and large vessel occlusions [LVOs]) with or without reperfusion therapies, limiting the overall relevance of the results. [22][23][24] In this context, we sought to investigate whether prestroke antihypertensive treatments (AHT) categorized as RAS inhibitors or non-RAS inhibitors influenced baseline stroke severity and neurological outcomes, in a homogeneous cohort of patients with AIS due to an anterior LVO and successfully treated by endovascular therapy (EVT).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized controlled trial comparing treatment with the ARB candesartan immediately following stroke or delayed until seven days later (ACCESS trial) there was no significant difference in functional outcome at three months, however early ARB treatment did significantly reduce the number of cardiovascular events [ 230 ]. An observational study of French stroke cohorts demonstrated no benefit of on-going ACEi or ARB treatment on stroke outcomes at 3 months [ 231 ]. However, in contrast to those studied described above, these patients also received thrombolysis with rt-PA. A meta-analysis of 26 clinical trials indicated that ARBs and ACEis offer no BP independent risk reduction for stroke [ 232 ].…”
Section: The Classical Ras In Strokementioning
confidence: 99%